2014
DOI: 10.1158/0008-5472.can-14-0389
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Heterogeneity of Breast Cancer Cells Is Associated with Expression of a Heterogeneous TGFβ-Activating miR424–503 Gene Cluster

Abstract: TGFb signaling is known to drive metastasis in human cancer. Under physiologic conditions, the level of TGFb activity is tightly controlled by a regulatory network involving multiple negative regulators. At metastasis, however, these inhibitory mechanisms are usually overridden so that oncogenic TGFb signaling can be overactivated and sustained. To better understand how the TGFb inhibitors are suppressed in metastatic breast cancer cells, we compared miRNA expression profiles between breast cancers with or wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 48 publications
(55 reference statements)
1
24
0
Order By: Relevance
“…We focused on miR-503 , which was strongly upregulated in the T/E VI only (∼7-fold), but not in the T/E III only microarray dataset (Supplementary Table 1). A search for potential miR-503 targets using in silico prediction algorithms showed that miR-503 could target SMAD7 [28], which was downregulated in T/E VI, but upregulated in T/E III cells. We therefore hypothesized that miR-503 might be a candidate modulating the biological activity of the T/E VI fusion variants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on miR-503 , which was strongly upregulated in the T/E VI only (∼7-fold), but not in the T/E III only microarray dataset (Supplementary Table 1). A search for potential miR-503 targets using in silico prediction algorithms showed that miR-503 could target SMAD7 [28], which was downregulated in T/E VI, but upregulated in T/E III cells. We therefore hypothesized that miR-503 might be a candidate modulating the biological activity of the T/E VI fusion variants.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the miR-503 -mediated downregulation of SMAD7 in T/E VI, but not in T/E III cells, explains T/E VI variant-specific transcription. Recently, Li et al could show that miR-503 downregulates SMAD7 expression and thereby enhances TGF-β signaling and the metastatic capability of breast cancer cells [28]. SMAD7-mediated stabilization of β-catenin binding to E-cadherin turned out to increase cell-cell adhesion and formation of adherens junctions [53], thereby potentially blocking metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have achieved a better understanding of the genetic alterations in CRC in recent years, the prognosis of CRC patients remains poor because of cancer cell invasion and distant metastasis [24], which result from the inherent heterogeneity and complex gene interactions of CRC [25]. Accordingly, discovering new biological mechanisms and novel regulators of CRC will provide a better approach for controlling CRC development [4].…”
Section: Discussionmentioning
confidence: 99%
“…As an oncogenic miRNA, miR‐106b‐25 can down‐regulate SMAD7 protein, which is well recognized that mediates destruction of the TGF‐β receptor 1(TGF‐βR1), resulting in elevated levels of the TGF‐βR1 and triggers TGF‐β pathway in breast tumor cells (Gong et al, ; Smith et al, ). Y. Li et al () reported the expression of miR‐424/503 cluster is elevated in metastatic breast tumor. Both miR‐424 and miR‐503 restrain SMAD7 and Smad ubiquitination regulatory factors (Smurf—two negative regulators of TGF‐β signaling—then resulted in the hyperactivation of this signaling pathway and enhance breast tumor metastasis (Y. Li et al, ).…”
Section: Crosstalk Between Various Signaling Pathways and Mirnas In Bmentioning
confidence: 99%
“…Y. Li et al () reported the expression of miR‐424/503 cluster is elevated in metastatic breast tumor. Both miR‐424 and miR‐503 restrain SMAD7 and Smad ubiquitination regulatory factors (Smurf—two negative regulators of TGF‐β signaling—then resulted in the hyperactivation of this signaling pathway and enhance breast tumor metastasis (Y. Li et al, ). MiR‐21 boosts migration and invasion of breast tumor cell induced by TGF‐β and epidermal growth factor (EGF).…”
Section: Crosstalk Between Various Signaling Pathways and Mirnas In Bmentioning
confidence: 99%